CONSIGNMENT STOCKING OF METALLURGICAL MATERIALS – A TOOL TO BUILD PARTNERSHIPS IN THE CHAIN - Pecinová, Zuzana; Branská, Lenka; Vávra, Jan (TANGER, spol. s r.o., 2016)
Processors of materials supplied by business of the metallurgical industry often seek to stabilize supplier-customer relationships with those suppliers who are able to supply metallurgical materials in a constant technical quality. This creates scope for finding an appropriate replenishment system for buyers of metallurgical materials. However, if the demand in a given chain is highly variable and unpredictable in essence, we cannot successfully implement modern methods used to control material flow in the chain, such as Quick Response, CPFR and other methods. It is necessary to look for alternative solutions, which is advantageous for both sides though – it suits customers, especially in terms of their requirements for readiness of inventory for their own production processes, and it also suits suppliers - especially in terms of the specifics of their own production processes. Consignment stocking appears to be a suitable solution in chains with products in the metallurgical industry. Its application taking into account the needs of both suppliers and buyers can be instrumental in building partnerships. The paper presents the results of qualitative research, implemented in 2015 in a company purchasing metallurgical materials, which applies consignment stocking in cooperation with the supplier. It presents a method to apply consignment stocking, its advantages and disadvantages while evaluating it with respect to its role in building partnerships in chains with metallurgical materials.
Konsignační skladování metalurgických material - nástroj budování partnerství v řetězci
Keywords: Supply chain; supplier; consignment; stocking; metallurgy; Dodavatelský řetězec; dodavatel; konsignační skladování; zásoby, metalurgie